Qawaid al-Fiqhiyyah Analysis on the Prohibition of Monopoly Practices and Unfair Business Competition: A Critical Review - Ahmad Lutfi Rijalul Fikri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
Qawa'id Al-Fiqhiyyah is essential in identifying new problems that arise for analysis, whether they follow Islamic law or not. The purpose of forming qa'idah-qa'idah in realizing Maqashid al-Sharia in protecting community property rights must be implemented in every statutory regulation or established by the government. This article examines and analyzes the prohibition of monopolistic practices and unfair business competition in Law No. 5 of 1999 using several qawa'id al-fiqhiyyah. This paper's study is based on literature data analyzed using qualitative research methods with a multidisciplinary approach. This study concludes that the Law on the prohibition of monopoly and unfair business competition in Law No. 5 of 1999, which contains the prohibition of control of production and marketing, the prohibition of fraud/ conspiracy, and the prohibition of using a dominant position under qawa'id al-fiqhiyyah, among others, namely the rules that say La Yahtakiru illa Khathi'un, an-Najasyu Haramun, and at-Tas'ir. The conformity of the objectives of laws and regulations with the establishment of qa’idah-qa’idah is something that the government must maintain in the Draft Law on the Prohibition of Monopolistic Practices and Unfair Business Competition, which is being programmed by the House of Representatives (DPR) of the Republic of Indonesia, so the purpose of being able to maintain community property rights can be implemented in this Law.